Application Mobile Health For Education And Prevention Stunting - Mayasari, Shinta; Nafisah Isnawati; Khrisna Agung Cendekiawan (Sean Institute, 2024)
Background: Stunting is a chronic nutritional problem that can interfere with a child's growth because it causes the child's height to not match his age or to be shorter. In 2021, Jember was ranked second in the East Java region with a score of 37.08%. ANTING is a mobile health-based Stunting Care Pharmacist which contained educational features and stunting prevention, one of which is through fulfilling clinical nutrition. Research Objective: The purpose of this study was to measure the increase in knowledge of families of stunting patients through mobile health-based education. Methods: This research was conducted at a health service facility in one of the sub-districts of Jember district. The research target was the families of stunting patients. This research used a quasy experiment with one group, pre and post test design. Researchers will carry out pre-test measurements from the beginning of the measurement and post-test on the same group at the last measurement. The sampling technique was accidental sampling for one month with a total of 32 samples. Results: The results of the study showed that there was an increase in the knowledge of stunting patients' families after receiving education through the media of mobile health applications which is marked p value 0,004.Conclusions: This ANTING provided some information related to stunting, especially in terms of preventing stunting, so that it has a positive effect on reducing the development of stunting rates.